Time Management Strategies as Determinants of Lecturers’ Job performance in Colleges of Education in Kwara State, Nigeria. - Mustapha, Mustapha, Adam Ishola; Yusuf, Suleiman; Yusuf, Laro Ibrahim; Aloba, Fatimah Musa (International Journal of Educational Management, 2021)
Time is one of the basic resource crucial to academic success and lecturers are expected to prudently utilize it rather than wasting it on tricky events. Thus, the study examined time management strategies as determinant of lecturers’ job performance in Colleges of Education in Kwara State, Nigeria. Descriptive research design was adopted for the study. The ]opulation of the study comprised all the 375 lecturers from the three Public Colleges of Education in Kwara State, Nigeria. Proportional sampling technique was used to select 120 lecturers from Colleges of Education, Ilorin, Lafiagi and Oro. Time Management Questionnaire “(TMQ) and Lecturers Job Performance Questionnaire (LJPA)” were used to elicit relevant information from the respondents. Three research hypotheses were postulated and tested using Pearson’s product moment correlation statistic at 0.05 level of significance. The instruments were validated by experts with reliability coefficient of 0. 73 and 0.84 for TMSQ and JPQ respectively through the use of test re-test method. The findings of the study revealed that there was significant relationship between time management strategies and lecturers’ job performance in Colleges of Education in Kwara State, Nigeria. It was recommended among others that lecturers’ should ensure prudent management their limited time by attending there classes as and when due for effective job performance in schools. Also, the principles of time management should be adopted by lecturers’ to perform their pedagogical tasks with efficacy and credibility. The management of the school should ensure that the institution’s time table is strictly followed by all academic staff through proper monitoring and supervision.